Pengaruh Inovasi Produk Terhadap Penjualan Coklat Berhantu pada Mf Dessert - Nur’aziza; Santi Yunus; Kalvin Parinding; Nuryana Haprin DJ Achmad; Rita Yunus (ManBiz: Journal of Management and Business, 2024)
Innovation is a mechanism for companies to adapt to a dynamic environment. Therefore, companies must be able to develop new thoughts and ideas, provide innovative products, and improve services to satisfy customers. This research aims to determine the effect of product innovation on sales of Haunted Chocolate at MF Dessert in Palu City. This study used descriptive qualitative method. The results show that in August, sales were relatively high due to product introductions to customers. However, in September and October, sales declined before the innovation was implemented, mainly due to a decrease in interest in sweets. After the innovation was implemented, sales in November and December increased because customers were attracted to the new flavors, many preferring pandan and cappuccino flavors to the original flavors. In conclusion, sales of Haunted Chocolate before the innovation had decreased due to lack of interest in sweet foods. Innovation has a positive effect on sales, as evidenced by an increase in sales after the innovation is implemented.